Answer:
Simplifying
2(3x + 3) = (2x + 2)
Reorder the terms:
2(3 + 3x) = (2x + 2)
(3 * 2 + 3x * 2) = (2x + 2)
(6 + 6x) = (2x + 2)
Reorder the terms:
6 + 6x = (2 + 2x)
Remove parenthesis around (2 + 2x)
6 + 6x = 2 + 2x
Solving
6 + 6x = 2 + 2x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-2x' to each side of the equation.
6 + 6x + -2x = 2 + 2x + -2x
Combine like terms: 6x + -2x = 4x
6 + 4x = 2 + 2x + -2x
Combine like terms: 2x + -2x = 0
6 + 4x = 2 + 0
6 + 4x = 2
Add '-6' to each side of the equation.
6 + -6 + 4x = 2 + -6
Combine like terms: 6 + -6 = 0
0 + 4x = 2 + -6
4x = 2 + -6
Combine like terms: 2 + -6 = -4
4x = -4
Divide each side by '4'.
x = -1
Simplifying
x = -1
Explanation: